PENGARUH COUNTER PRESSURE TERHADAP NYERI PERSALINAN KALA I FASE AKTIF - Berliana Irianti; Nur Israyati Israyati (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Labor pain methods can be applied pharmacologically and non-pharmacologically. Labor pain is something that is commonly felt by pregnant women just before the birth process. But if it is not treated with proper pain management, it will cause other problems, one of which is anxiety. The aim of the study was to determine the Effectiveness of Counter Pressure on Pain Levels in Active Phase I Labor at Independent Midwife Practice (PMB) in Hasna Dewi, Pekanbaru City. This type of research is pre-experimental with two group pretest and posttest designs. The time of research was carried out in August-November 2022. The sample in this study was 10 respondents using a total sampling technique. The research instrument used a Numerical Rating Scale (NRS) questionnaire. Univariate and bivariate data analysis. The univariate results obtained pain before being given a moderate pain counter pressure with a percentage of 80.0%. pain after being given counter pressure pain decreased to mild pain with a percentage of 80.0%. Wilcoxon Rank Test results. There is an effect of counter pressure on the level of pain in the first active phase of labor with a P value of 0.002 <0.05. So it can be concluded that there is an effect of counter pressure on the level of pain in the active phase of labor in the first stage. It is recommended for health workers to be able to use counterpressure to reduce pain in the first active phase of labor.